2019
DOI: 10.1007/s00285-019-01393-w
|View full text |Cite
|
Sign up to set email alerts
|

A gradient flow formulation for the stochastic Amari neural field model

Abstract: We study stochastic Amari-type neural field equations, which are mean-field models for neural activity in the cortex. We prove that under certain assumptions on the coupling kernel, the neural field model can be viewed as a gradient flow in a nonlocal Hilbert space. This makes all gradient flow methods available for the analysis, which could previously not be used, as it was not known, whether a rigorous gradient flow formulation exists. We show that the equation is well-posed in the nonlocal Hilbert space in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
(91 reference statements)
0
2
0
Order By: Relevance
“….). It has been proven that (73) has many analogies to classical local (S)PDEs [108,111]. Furthermore, travelling waves have been studied, particularly in the bistable case, in quite some detail for stochastic neural fields, see e.g.…”
Section: Discussionmentioning
confidence: 99%
“….). It has been proven that (73) has many analogies to classical local (S)PDEs [108,111]. Furthermore, travelling waves have been studied, particularly in the bistable case, in quite some detail for stochastic neural fields, see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore biology is typically very noisy, and thus it is of great importance to understand the effect of stochasticity on these patterns and waves [75,66,79]. The literature on stochastic patterns and waves includes general Turing patterns [10], the Allen-Cahn / Cahn-Hilliard equation [43], waves and patterns in the stochastic Brusselator [8,9], patterns in neural fields [49,38,56,41,85,2,62,16,70], interfaces in the Ginzburg-Landau equation [13,48], the stochastic burger's equation [12] and the effect of spatially-distributed noise on traveling waves [72,1,23], such as the FKPP traveling waves [29,20], invasion waves in ecology [64], the stochastic Nagumo equation [59,47,39], geometric waves [90] and numerical methods for stochastic traveling waves [68]. Good reviews of the literature on the effect of noise on traveling waves can be found in [75,79,60].…”
Section: Introductionmentioning
confidence: 99%